Towards a class compromise in South Africa's "double transition": bargained liberalization and the consolidation of democracy - Webster, Edward; Adler, Glenn (University of the Witwatersrand. History Workshop., 1999)
South Africa's 1994 settlement ensured the survival of one of the world's most unequal capitalist systems. Liberals liked that it was based on the international economic order. All that changed was the inclusion of a few Blacks in the economic power of the White corporate elite. Change came though a conservative pact. What is needed is a class compromise which allows for engaging in the global economy but limits economic liberalisation, i.e. bargained (limited) liberalization not complete economic liberalization.
Paper presented at the Wits History Workshop: Forging the links between historical research and the policy process, 18-19 September 1999.
Keywords: Politics and government. South Africa; Democracy. South Africa; Social conditions. South africa; Economic conditions. South Africa